Early risk indicators (0-36 months) of autism spectrum disorder. A review of the literature - Raúl Tárraga Mínguez; Irene Lacruz-Pérez; Gemma Pastor-Cerezuela; María-Inmaculada Fernández Andrés (INFAD, 2018)
The prevalence of the autism spectrum disorder (ASD) has increased significantly in the recent years mainly due to an increase in the knowledge of the professionals responsible of its identification and/or diagnosis. The objective of the current study is to review the articles published in 2018 that have attempted to identify reliable predictors (between 0 and 36 months of life) of the subsequent onset of ASD. A search was conducted in PsycInfo in which 8 empirical studies designed to assess the predictive power of these early indicators were found. In these studies were identified different symptoms that are considered reliable predictors of the subsequent diagnosis of ASD, such as the existence of differences in the sensory profile compared to children without ASD, the visual perception of social stimuli and differences in the ability of directing the attention and the acquisition of fine motor skills.